Pendampingan Pemasaran Produk Lokal Desa Untuk Meningkatkan Daya Saing Di Pasar Global Di Desa Klambir V Kebun - Amelia, Ocdy; Sulardi, Sulardi; Putra, Hardiansyah (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Community service is an obligation that must be carried out by every lecturer in higher education. The activity carried out by the UNPAB Service Team was entitled Marketing Assistance for Village Local Products to Increase Competitiveness in the Global Market in Klambir V Kebun Village. Based on the problems presented are the limited human resources skilled in global marketing, low knowledge of the international market, limited capital to support business expansion, and bureaucratic obstacles in the export process. The assistance carried out needs to focus on overcoming these obstacles by providing practical solutions. To compete in the global market, product quality is one of the key factors. Assistance in terms of improving product quality is very important, both in terms of raw materials, production processes, and packaging. Klambir V Kebun Village needs to ensure that the products produced meet the quality standards required by the global market, which often prioritizes safety and sustainability aspects.